Rebirth of a reef: As-built description and rapid returns from the Palos Verdes Reef Restoration Project - Williams, Jonathan P.; Williams, Chelsea M.; Pondella, Daniel J.; Scholz, Zoe M. (Frontiers in Marine Science, 2022)
Palos Verdes Reef (PVR) is an artificial reef designed to restore rocky-reef associated marine species by directly restoring rocky-reef habitat that has been impacted by scour, sedimentation, and burial in the shallow subtidal portion of the Palos Verdes Peninsula in Los Angeles County, California, USA. The restoration reef provides high-quality habitat that is contiguous with the natural reef and allows for rapid succession. This project is a unique endeavor as restoring lost habitat in situ and has not been attempted in a temperate rocky reef and kelp forest community. While the primary design criteria for PVR is fish production in an area where already-limited hard substrate had been lost, it is also designed to be resilient to ongoing sedimentation and turbidity challenges on the peninsula. Following over a decade of design, planning, outreach, site surveying, and permitting, PVR was built in 2020 as 18 discrete modules using 52,729 tons of quarry rock placed approximately 8–80 m from existing, unburied rocky-reef habitat. There was no significant accumulation or scouring of sediment due to the placement of the reef and temperature data shows that internal tides regularly inundate the reef with cool, nutrient rich water. Rocky-reef associated taxa rapidly recruited to the restoration site, with visible changes occurring within just a few months post-construction. PVR modules showed rapid, significantly positive responses in fish density, fish biomass, kelp density, and biotic benthic cover less than 18 months after reef placement with a general pattern of succession in giant kelp growth from nearshore to offshore resulting in an established, thick canopy, in the nearshore, shallow modules. The newly available, high-quality habitat was quickly colonized and already shows late successional patterns with respect to fish and benthic communities. This restoration reef will produce large amounts of biomass over the long-term, though future surveys of multiple restored, adjacent, and reference sites will determine if high biomass at PVR is a result of new secondary production or attraction from nearby reefs.